The coping strategies used over a two-year period by HIV-positive women who had been diagnosed during pregnancy. - Kotzé, Marinda; Visser, Maretha; Makin, Jennifer; Sikkema, Kathy; Forsyth, Brian (AIDS care, 2013)
Abstract Structured interviews were conducted with 224 HIV-positive women diagnosed during pregnancy, at antenatal clinics in Tshwane, South Africa, in order to investigate the use of coping strategies during the first two years after diagnosis. Interviews were conducted between one and four weeks after diagnosis during pregnancy, with three follow-up interviews conducted post-partum. Coping strategies were assessed with an adapted version of the Brief COPE. It was found that active coping was used more often than avoidant coping throughout the study period. Active coping increased over time, while avoidant coping decreased at first but increased again between 6 and 21 months after diagnosis. The most frequently used coping strategies included acceptance, direct action, positive reframing, religion and distraction. At first, women coped through internalised strategies. Over time, outward-focused strategies developed. Avoidant coping patterns differed from previous research indicating that women diagnosed during pregnancy deal with the consequences of HIV after the baby is born. Recommendations for mental health services are made.